Role of Nuclear Receptors, Lipid Metabolism, and Mitochondrial Function in the Pathogenesis of Diabetic Kidney Disease - Hughes, Eleni; Wang, Xiaoxin X.; Sabol, Lily; Barton, Keely; Hegde, Sujit; Myakala, Komuraiah; Krawczyk, Ewa; Rosenberg, Avi Z.; Levi, Moshe (American journal of physiology. Renal physiology, 2025)
Diabetic kidney disease (DKD) is a leading cause of end-stage renal disease (ESRD) and remains a significant clinical challenge due to its complex pathogenesis. This review explores the intricate interplay of metabolic, inflammatory, and cellular mechanisms that drive DKD progression, with a particular focus on lipid metabolism, mitochondrial dysfunction, oxidative stress, inflammation, cell injury, and epigenetic modifications. Advances in histopathological and molecular studies have expanded our understanding of glomerular, tubular, and vascular abnormalities in DKD, highlighting the critical role of nuclear hormone receptors, transcription factors, and G protein-coupled receptors in regulating renal lipid accumulation, mitochondrial function, inflammation, oxidative stress, and fibrotic pathways. Additionally, emerging evidence implicates novel cell death mechanisms, including ferroptosis, necroptosis, pyroptosis, and PANoptosis, in DKD pathology. Epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNAs, further contribute to disease progression by regulating gene expression in response to metabolic stress. As current therapeutic strategies remain insufficient to prevent DKD progression, this review also discusses novel molecular targets and emerging therapeutic approaches aimed at mitigating lipid toxicity, enhancing mitochondrial function, and suppressing inflammation. By integrating insights from histopathology, molecular biology, and translational research, this review provides a comprehensive framework for developing future strategies to delay or prevent DKD progression.